2018
DOI: 10.7150/jca.21187
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic salpingectomy at benign gynecological surgery for reducing ovarian cancer risk: a 10-year single centre experience from China and a literature review

Abstract: Current evidences indicate that the fallopian tube plays a major role in the pathogenesis of epithelial ovarian cancer (EOC). Salpingectomy represents a novel and potentially effective risk-reducing option. In this study, there were 1822 patients diagnosed and treated for EOC or primary peritoneal cancer (PPC) at Department of Gynecologic Oncology, Tianjin Medical University Cancer Institute and Hospital from January 1, 2007 to April 30, 2017. Among them, 198 patients with a history of gynecological surgery be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
(23 reference statements)
0
6
0
2
Order By: Relevance
“…Prophylactic salpingectomy at the time of hysterectomy for benign disease was applied to women in 70–80% of institutions accredited by an academic society and in 50–65% of institutions not accredited by an academic society in Japan [ 54 ]. In China, the rate of bilateral salpingectomy increased threefold (from 22% to 60%) from 2007 to 2017 [ 55 ]. Corresponding data from Korea are unavailable.…”
Section: Other Position Statements On Prophylactic Salpingectomy and mentioning
confidence: 99%
“…Prophylactic salpingectomy at the time of hysterectomy for benign disease was applied to women in 70–80% of institutions accredited by an academic society and in 50–65% of institutions not accredited by an academic society in Japan [ 54 ]. In China, the rate of bilateral salpingectomy increased threefold (from 22% to 60%) from 2007 to 2017 [ 55 ]. Corresponding data from Korea are unavailable.…”
Section: Other Position Statements On Prophylactic Salpingectomy and mentioning
confidence: 99%
“…In a case-controlled study by Chen et al, patients diagnosed with epithelial ovarian cancer or primary peritoneal cancer who had previously undergone benign gynecologic procedures were compared to casematched controls. 4 The incidence of cancer was significantly decreased in patients who underwent salpingectomy, compared to those whose fallopian tubes remained in situ ( p < 0.05) 4 Various studies have demonstrated feasibility, safety, and financial benefit of performing an OBS during a vaginal surgery. In 2 prospective studies of women undergoing vaginal hysterectomy, primarily for POP, a vaginal salpingectomy was performed successfully in 73.9% and 81% of cases, respectively 5,6 Risk factors for failure included older age, menopausal status, and elevated body mass index, as well as prior adnexal surgery and uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…В качестве превентивной тактики необходимо минимизировать влияние факторов-модификаторов пенетрантности мутаций, таких как использование внутриматочных девайсов, заместительная гормональная терапия, курение, ожирение. Профилактическая билатеральная овариоэктомия ассоциирована со значительным снижением риска развития и показателей смертности от РЯ у носительниц мутаций в генах ВRСА1, 2 [49,50]. Однако доказательная база эффективности данного метода хирургической профилактики при обнаружении мутаций в других генах-кандидатах на сегодня отсутствует.…”
Section: молекулярно-генетическое тестирование при ряunclassified